ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGABDOPSIAN E-COMMERCEDI KELURAHAN CEPOGO BOYOLALI - Prasetya, Adhitya Yoga (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
E-commerce has been giving a lot of benefits to small and mediumenterprises (SMEs), but there are only a few SMEs which have adopted it.Therefore, it is necessary to find out what are the factors that support SMEsto adopt E-commerce. So far, researches on E-commerce have been done onforeign-large-scale businesses, while researches on SMEs especially about theadoption of E-commerce have been a few. That is why this research willdiscuss the adoption of E-commerce on Indonesian SMEs and will includethe factors that support E-commerce adoption. The problems in this researchare elaborated into research questions, i.e. do, top management support,organizational readiness, external pressure, and perceived benefits havesignificant positive effect to E-commerce adoption? And does the adoptionhave significant positive effect to company’s performance? The purpose ofthis research is to analyze factors that support E-commerce adoption onIndonesian SMEs and to analyze whether the adoption improves theperformance of the SMEs. This technique is chosen because it is the secondgeneration of multivariate analyzing technique that enables researchers totest the relation between complex variables to get an overall view of thewhole model. Besides, SEM can also test a series of a complicated relationsimultaneously. The results of this research explain that top managementsupport, organizational readiness, external pressure, and perceived benefitshave Significant positive effect to E-commerce adoption, and the adoptionhave significant positive effect to company’s performance.